THE INFORMATION SEEKING BEHAVIOUR MODEL OF IPB UNIVERSITY STUDENTS BASED ON STRUCTURAL EQUATION MODELLING - Dr. Ir. Janti G. Sujana, MA (Perpustakaan IPB, 2019)
The abundant of information on the internet has become a competitor for libraries as information service providers. Therefore to survive and thrive, the libraries must change and adopt to a rapidly evolving external environment. Understanding user information seeking behaviour is very useful for redesigning various services that suit to user needs. The objectives of this study were: 1). To analyze the characteristics of digital natives and digital immigrants of IPB University students related to their information seeking behaviour; 2). To develop a model of information seeking behaviour of both digital natives and digital immigrants of IPB University students based on structural equation modeling. The study was mainly quantitative and questionnaire was designed to study students’ information-seeking behaviour. The findings showed that the dominant behaviours and preferences of digital natives in their information seeking behaviour were influenced by environmental variables, especially the availability of information. For the information seeking behaviour variables of students, the dominant indicator were asking for printed and digital information to the lecturer. While for immigrant digital students their information seeking behaviour were dominantly influenced by environmental variables, especially the availability of information. The indicators for information seeking behaviour of digital immigrant student were dominated by asking printed information to friends, and requesting digital information to the lecturer. The success of getting information is dominant in the speed-of-getting-information indicator, both for digital natives and digital immigrant students.